Regulation of Vascular Endothelial Growth Factor Receptor-2 Activity by Caveolin-1 and Plasma Membrane Cholesterol - Labrecque, Lyne (The American Society for Cell Biology, 2003)
The stimulation of vascular endothelial growth factor receptor-2 (VEGFR-2) by tumor-derived VEGF represents a key event in the initiation of angiogenesis. In this work, we report that VEGFR-2 is localized in endothelial caveolae, associated with caveolin-1, and that this complex is rapidly dissociated upon stimulation with VEGF. The kinetics of caveolin-1 dissociation correlated with those of VEGF-dependent VEGFR-2 tyrosine phosphorylation, suggesting that caveolin-1 acts as a negative regulator of VEGF R-2 activity. Interestingly, we observed that in an overexpression system in which VEGFR-2 is constitutively active, caveolin-1 overexpression inhibits VEGFR-2 activity but allows VEGFR-2 to undergo VEGF-dependent activation, suggesting that caveolin-1 can confer ligand dependency to a receptor system. Removal of caveolin and VEGFR-2 from caveolae by cholesterol depletion resulted in an increase in both basal and VEGF-induced phosphorylation of VEGFR-2, but led to the inhibition of VEGF-induced ERK activation and endothelial cell migration, suggesting that localization of VEGFR-2 to these domains is crucial for VEGF-mediated signaling. Dissociation of the VEGFR-2/caveolin-1 complex by VEGF or cyclodextrin led to a PP2-sensitive phosphorylation of caveolin-1 on tyrosine 14, suggesting the participation of Src family kinases in this process. Overall, these results suggest that caveolin-1 plays multiple roles in the VEGF-induced signaling cascade.